Peningkatan Kepesertaan Aktif Jaminan Sosial Ketenagakerjaan Berbasis Ketahanan Dana - Yayat Syariful Hidayat; Popong Nurhayati; Yudha Heryawan Asnawi; Mohamad Rhesa Adisty (Journal of Economics and Management Scienties, 2026)
Increasing employment social security coverage is a fundamental prerequisite for achieving Universal Social Security Coverage. However, the upward trend in membership, accompanied by rising claim ratios, poses significant challenges to fund sustainability. This study aims to analyze the impact of active membership coverage on the fund sustainability of BPJS Ketenagakerjaan and identify the influencing factors within the Old Age Security (JHT), Pension Security (JPN), Work Injury Security (JKK), and Death Security (JKM) programs. This research employs a quantitative method with a desk research approach, utilizing national secondary data sourced from the Actuarial and Social Security Research Deputy of BPJS Ketenagakerjaan. Data analysis was conducted using multiple linear regression via STATA software to examine the effects of several variables: number of cases, claim nominals, active participants, total contributions, and average participant age on fund sustainability. The findings reveal diverging patterns across the programs. In non-insurance schemes (JHT and JPN), the number of active participants and total cases exert a positive influence on fund sustainability. Conversely, in insurance-based schemes (JKK and JKM), the number of participants and average participant age show a negative correlation with fund sustainability. This study concludes that membership expansion must be balanced with risk management and fund sustainability strategies tailored to the specific characteristics of each program.